Analysing the Relationship Between Mental Load or Mental Effort and Metacomprehension Under Different Conditions of Multimedia Design - Schnaubert, Lenka; Schneider, Sascha (Frontiers in Education, 2022)
Cognitive load theory assumes effort may only lead to comprehension if the material-induced load leaves enough resources for learning processes. Therefore, multimedia materials should induce as little non-relevant load as possible. Metacognition research assumes that learners tap into their memory processes to generate a mental representation of their comprehension to regulate learning. However, when judging their comprehension, learners need to make inferences about actual understanding using cues such as their experienced mental load and effort during learning. Theoretical assumptions would assume both to affect understanding and its metacognitive representation (metacomprehension). However, the question remains how perceived effort and load are related to metacomprehension judgments while learning with multimedia learning material. Additionally, it remains unclear if this varies under different conditions of multimedia design. To better understand the relationship between perceived mental load and effort and comprehension and metacomprehension under different design conditions of multimedia material, we conducted a randomized between-subjects study (N = 156) varying the design of the learning material (text-picture integrated, split attention, active integration). Mediation analyses testing for both direct and indirect effects of mental load and effort on metacomprehension judgments showed various effects. Beyond indirect effects via comprehension, both mental load and effort were directly related to metacomprehension, however, this seems to vary under different conditions of multimedia design, at least for mental effort. As the direction of effect can only be theoretically assumed, but was not empirically tested, follow-up research needs to identify ways to manipulate effort and load perceptions without tinkering with metacognitive processes directly. Despite the limitations due to the correlative design, this research has implications for our understanding of cognitive and metacognitive processes during learning with multimedia.